1982
DOI: 10.1111/j.1399-0004.1982.tb02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cytogenetic aspects of X‐chromosome deletions

Abstract: Karyotype/phenotype correlations in six non‐mosaic patients with dysgenetic ovaries and partial deletions of the X‐chromosome (three patients with short arm, and three with long arm deletions) are presented and the pertinent literature is analysed. It would appear that functioning ovarian tissue is present more often in patients with a short arm deletion than in those with a deleted long arm. This may represent a difference in the strength of two sets of controlling factors, but it can also be related to break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Deletion involving the long arm of X chromosome generally results in ovarian failure if they involve the proposed critical region Xq13-q26. [17] In our study, it was evidenced that eight subjects had X chromosome structural abnormalities of partial monsomy/trisomy 46,X,del (Xp), 46,X, del(X)q, 46,X ring(X), and 46,X,iso(X) as shown in Figure 1a–h.…”
Section: Discussionmentioning
confidence: 67%
“…Deletion involving the long arm of X chromosome generally results in ovarian failure if they involve the proposed critical region Xq13-q26. [17] In our study, it was evidenced that eight subjects had X chromosome structural abnormalities of partial monsomy/trisomy 46,X,del (Xp), 46,X, del(X)q, 46,X ring(X), and 46,X,iso(X) as shown in Figure 1a–h.…”
Section: Discussionmentioning
confidence: 67%
“…Central obesity might contribute to the increased metabolic risk 10–12 . Correlations between different karyotypes and phenotypic characters have been demonstrated, but knowledge regarding genotype and phenotype correlations in TS is poor, especially in those with mosaicism 13–19 . In those older studies, however, only a few cells were used in the karyotyping process.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been made to correlate the type of X chromosome anomaly such as totally missing chromosome X (45X), aberrations of chromosome X (partial deletions of short and long arms, isochromosomes) and various mosaicisms in group of Turner syndrome individuals with their clinical features (Kusiak et al , 2000, 2005). The classical abnormalities of Turner syndrome include many somatic anomalies, such as short stature, infantile external genitalia, webbed neck, cubitus valgus, low hairline, shield‐like chest, anomalies in the structure of some internal organs and others (Turner, 1938; Horowitz and Morishima, 1974; Palmer and Reichmann, 1976; Arulanantham et al , 1980; Jaspers and Witkop, 1980; Goldman et al , 1982; Hall and Gilchrist, 1990; Lippe, 1991; Pelz et al , 1991; Temtamy et al , 1992; Robinson and de la Chapelle, 1996; Lopez et al , 2002). Some oral abnormalities were also observed, such as malocclusion (Harju et al , 1989; Laine et al , 1992; Szilagyi et al , 2000), early development of permanent teeth (Filipsson et al , 1965), high‐arched palate (Horowitz and Morishima, 1974), small teeth (Townsend et al , 1984; Varrela et al , 1988; Mayhall et al , 1991; Mayhall and Alvesalo, 1992; Midtbo and Halse, 1994a,b; Townsend and Alvesalo, 1995; Kusiak et al , 2000; Szilagyi et al , 2000; Zilberman et al , 2000), crown hypoplasia (Lopez et al , 2002), abnormalities in intercuspal distance (Lopez et al , 2002) and abnormality of root morphology of mandibule were also observed (Varrela, 1990, 1992; Lopez et al , 2002; Kusiak et al , 2005).…”
Section: Introductionmentioning
confidence: 99%